Analisis Partisipasi Siswa Dalam Keterlibatan OSIS Sebagai Wadah Memperkukuh Sifat Demokratis di SMP Negeri 25 Samarinda - Eki, Lusia; Pardosi, Jawatir; Asnar, Asnar; Warman, Warman; Suryaningsi, Suryaningsi; Wingkolatin , Wingkolatin (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
The aim of the research is to determine whether student participation in OSIS activities can strengthen the nature of democracy and to determine the school's efforts to foster a spirit of participation through strengthening democracy in OSIS activities. This type of research is descriptive qualitative. The subjects of this research were PPKn teachers, OSIS supervisors, OSIS members and students using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, and data conclusion. The research results show that student participation in various activities or programs can strengthen students' democratic nature, such as through student participation in the OSIS, students can learn about responsibility, cooperation and collective decision making. Apart from that, students who are actively involved in OSIS activities will better understand the importance of participation and contribution in an organization and also participation in the OSIS encourages students to be more open in communicating, conveying ideas, and accepting input from others, which is the essence of democratic nature. The school's efforts to foster a spirit of student participation through strengthening democracy in OSIS activities is an important strategy for forming students' character and social skills. Strengthening democracy is defined as the application of democratic values such as openness, active participation, responsibility, and respect for differences of opinion in the school environment.